An Intimate Rebuke: Female Genital Power in Ritual and Politics in West Africa By L. S. Grillo (2018). (24th July 2022) - Johnson, Michelle C
Abstract : An Intimate Rebuke: Female Genital Power in Ritual and Politics in West Africa By L. S. Grillo (2018) Durham: Duke University Press, ix + 284pp.